Comparison of in vivo targeting ability between cRGD and collagen-targeting peptide conjugated nano-carriers for atherosclerosis - Kim, Manse; Sahu, Abhishek; Kim, Gi Beom; Nam, Gi Hoon; Um, Wooram; Shin, So Jin; Jeong, Yong Yeon; Kim, In-San; Kim, Kwangmeyung; Kwon, Ick Chan; Tae, Giyoong (ELSEVIER SCIENCE BV, 2018)
Atherosclerosis plaque is a major cause of cardiovascular diseases across the globe and a silent killer. There are no physical symptoms of the disease in its early stage and current diagnostic techniques cannot detect the small plaques effectively or safely. Plaques formed in blood vessels can cause serious clinical problems such as impaired blood flow or sudden death, regardless of their size. Thus, detecting early stage of plaques is especially more important to effectively reduce the risk of atherosclerosis. Nanoparticle based delivery systems are recognized as a promising option to fight against this disease, and various targeting ligands are typically used to improve their efficiency. So, the choice of appropriate targeting ligand is a crucial factor for optimal targeting efficiency. cRGD peptide and collagen IV targeting peptide, which binds with the alpha(v)beta(3) integrin overexpressed in the neovasculature of the plaque and collagen type IV present in the plaque, respectively, are frequently used for the targeting of nanoparticles. However, at present no study has directly compared these two peptides. Therefore, in this study, we have prepared cRGD or collagen IV targeting (Col IV-tg-) peptide conjugated and iron oxide nanoparticle (IONP) loaded Pluronic based nano-carriers for systemic comparison of their targeting ability towards in vivo atherosclerotic plaque in Apolipoprotein E deficient (Apo E-/-) mouse model. Nanocarriers with similar size, surface charge, and IONP loading content but with different targeting ligands were analyzed through in vitro and in vivo experiments. Near infrared fluorescence imaging and magnetic resonance imaging techniques as well as Prussian blue staining were used to compare the accumulation of different ligand conjugated nano-caariers in the aorta of atherosclerotic mice. Our results indicate that cRGD based targeting is more efficient than Col IV-tg-peptide in the early stage of atherosclerosis.
Keywords: IRON-OXIDE NANOPARTICLES; VASCULAR INFLAMMATION; CONTRAST AGENTS; PLAQUE BURDEN; ALPHA(V)BETA(3); NANOMEDICINE; ANGIOGENESIS; EXPRESSION; RECEPTOR; QUANTIFICATION